The Bear beyond the ocean - Cadioli, Giovanni (Rivista di studi politici internazionali, 2022)
Since the year 2000 and the election of V. V. Putin as President of the Russian Federation, the international arena saw a fast and consistent rebirth of Russia as a global power. Most of the existing academic research in favor and against this statement have focused on the Eurasian geopolitical arena, partially neglecting the importance of another crucial area, the Latin American one. Central-South America represented a quasi-virgin land for the Russian Federation, which starting from the year 2000 succeeded in penetrating economically and politically the former ‘Us backyard’. Nations like Venezuela and Brazil are now decisive rings in the chain of Russia’s world alliances, while Us’ influence dramatically decreased in nearly whole the continent. The topic of Russian involvement in Latin America is analyzed as a three-stage process: first utilitarian economical contacts with a single State; then, further ones, with an increasing number of countries, motivated by geopolitical reasons and mutual-benefit consideration; and last the evolution of some of these contacts into solid political alliances. From Soviet involvement in Latin America up to Russia’s role in the Libyan and Syrian crisis, the analysis precisely demonstrates how the aim of Russia’s involvement in Latin America, the way it has proceeded and finally its results are some of the most important arguments to sustain that Russia has returned on the international arena as a strong, unavoidable global power.